PENGARUH PEMBERIAN AROMATERAPI LAVENDER TERHADAP PENURUNAN NYERI LUKA IBU POST SECTIO CAESAREA DI RST dr SOEPRAOEN KESDAM V/BRAWIJAYA MALANG - Prasetiyo, Bagus Dadang; Susilo, Bambang (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
Sectio caesarea always relate to incision causing trauma for the suf erer and causing multiple complaint and symptom. One of the most often complaint was pain. This research aimed to know the ef ect of lavender aromatheraphy for pain scale alteretion of mother with post sectio caesarea. The design of the research was pre experiment design with one group pre test-post test design. The population of the research was day one post sectio caesarea mother in 1-2 juny 2019. The sample was 8 post caesarea mother. Sampling thecnique used for this research was purposive sampling and the data analized with t test. The result of this research show before the aromatheraphy gifted to the respondent 100% of them experiencing moderate pain. After giving the aromatheraphy 62,5 % of respondents are in moderate pain and 37,5% are in mild pain. Analized data result that p value was 0,021 which is less than Î± (0,05) with the result that ho rejected and hi accepted, there is influence of lavender aromatheraphy for pain scale alteretion of mother with post sectio caesarea. Based on this research mother were suggested for apply this lavender aromatheraphyKeyword :Â pain intensity,Â lavender aromatheraphy,sectio caesareaÂ